Automobile Aftermarket Customization and its Trends with an Emphasis on the Potential for the Czech Market - Kosek, Vladimír (2016)
The aim of the thesis is to provide an overview of the automobile aftermarket customization and to evaluate its potential on the Czech market. The first goal is to understand why product design is crucial for consumers in general and to highlight its importance for automobile industry. Moving forward, the historical development of the automotive design with emphasis on external factors influencing technical and design development and, consequently customers preferences is provided. In order to analyze the potential of the customizing companies in the Czech Republic, a research among several Czech and German modifiers was conducted. The outcomes of the research enabled to draw the conclusions and evaluate the actual potential of automobile aftermarket modification.